- Thread starter
- #1

#### Albert

##### Well-known member

- Jan 25, 2013

- 1,225

$(0<x<3), \sqrt {1+x^2}+\sqrt {9+(3-x)^2} =5$

find :$x$

find :$x$

- Thread starter Albert
- Start date

- Thread starter
- #1

- Jan 25, 2013

- 1,225

$(0<x<3), \sqrt {1+x^2}+\sqrt {9+(3-x)^2} =5$

find :$x$

find :$x$

- Admin
- #2

- Feb 14, 2012

- 3,840

$(0<x<3), \sqrt {1+x^2}+\sqrt {9+(3-x)^2} =5$

find :$x$

$\sqrt {1+(\tan y)^2}+\sqrt {9+(3-\tan y)^2} =5$

$\sec y+\sqrt {9+(3-\tan y)^2} =5$

$\sqrt {9+(3-\tan y)^2} =5-\sec y$

Square both sides of the equation and simplify, we have:

$-3\tan y =4-5\sec y$

Squaring again and use the identity $1+(\tan y)^2=\sec^2 y$ we obtain:

$(4\sec y-5)^2=0$

In other words, $\sec y =\dfrac{5}{4}$ and this implies $\tan y= \dfrac{3}{4}$ or $x=\dfrac{3}{4}$.

- Admin
- #3

\(\displaystyle \sqrt{9+(3-x)^2}=5-\sqrt{1+x^2}\)

Both sides are positive, so squaring yields:

\(\displaystyle 9+(3-x)^2=25-10\sqrt{1+x^2}+1+x^2\)

Expand squared binomial and collect like terms:

\(\displaystyle 4+3x=5\sqrt{1+x^2}\)

Square again:

\(\displaystyle 16+24x+9x^2=25\left(1+x^2 \right)\)

\(\displaystyle 16x^2-24x+9=0\)

\(\displaystyle (4x-3)^2=0\)

\(\displaystyle x=\frac{3}{4}\)

- Thread starter
- #4

- Jan 25, 2013

- 1,225

$(0<x<3), \sqrt {1+x^2}+\sqrt {9+(3-x)^2} =5$

find :$x$